Relationship between transformation temperatures and alloying elements in Cu-Al-Ni shape memory alloys - Karagoz, Z.; Canbay, C. Aksu (Springer, 2013)
Cu-Al-Ni shape memory alloys are good candidates for high temperature applications. We have investigated the effects of alloying elements on transformation temperatures, heat-capacity values, and structural properties of Cu-13.73Al-4.3Ni and Cu-13Al-4.3Ni (wt%) shape memory alloys. The evolution of the transformation temperatures was studied by differential scanning calorimetry with different heating/cooling rates. The heat-capacity measurements of the samples were made. It was found that the mass percentage of the alloying element has an important effect on the characteristic transformation temperatures and thermodynamic parameters. The structural changes of the samples were studied by X-ray diffraction measurements and optical microscope observations at room temperature. It is evaluated that the transformation parameters of CuAlNi shape memory alloy can be controlled by the change of the mass percentages of the alloying elements.
Keywords: Shape memory alloy; Transformation temperatures; Heat capacity